Evaluation of mass housing settlements in terms of wind and noise control: Istanbul and Diyarbakir as a case - Gedik, Gülay Zorer; Akdağ, Neşe Yüğrük; Kiraz, Fatih; Şener, Bekir; Çaçan, Raşide (Journal of Environmental Engineering and Landscape Management, 2017)
In mass housing apartments, the comfort and quality of living conditions may be adversely affected by wind and noise especially on balconies, terraces, gardens and around swimming pools etc. The quantitative and empirical testing of building models according to physical conditions with regard to wind and noise parameters directly affects the formation of buildings in the design process. In this paper, two cities (Istanbul and Diyabakır), which are selected from two different climatic zones in Turkey are considered as examples to create maximum comfortable usage areas depending on wind and noise effects. For mass housing settlement scenarios, common comfortable areas in terms of wind and noise were determined by using Urbawind and soundplan softwares. The relevant data and acceptance criteria related to wind and noise and applied procedure are presented in the work. Performed studies show, if the settlements have dominant wind and noise directions, it is possible to find solutions using the geometric properties of the settlement in terms of wind and noise. In general, better comfort results appear in alternatives with L-C-U shaped design features rather than point-type and linear block layouts.